Sensoriality As A Thematic Of Architecture Of The Xxth Century In Algeria. - Zineddine, Sara; Belakehal, Azzedine (Journal of Architecture and environment of child, 2021)
In the aftermath of independence, Algeria experienced a succession of several architectural trends and styles. They were shaped on the one hand by the colonial power that lasted for more than a century, and having bequeathed structures on several scales in a continuity of many models during the first postcolonial period. On the other hand, these trends illustrate the impact of foreign architects, of international renown, who have participated enormously in: i) the construction of prestigious facilities, ii) the reconstruction of an architecture referring to identity, society, and Algerian culture, which underwent actions of erasure and substitution during the colonial period, and iii) the creation of contemporary Algerian architecture. The presence of the latter is visible throughout the Algerian territory as evidenced by all these sites, buildings, and monuments still standing today. In this sense, the objective of this research is to present various projects of Algerian architecture of the post-independence period. He mainly evokes the question of the sensory dimension, and the way in which the architects have integrated it, clearly and / or implicitly, within the architectural space by means of multiple architectural devices. Thus, it will be a question of exploring the interest given to the different atmospheres of the space built according to visual, tactile, auditory, and olfactory stimuli ... etc. An extensive review of the related literature, personal in-situ observations as well as the thematic analysis of the architects' discourse constitute the methodological arsenal to achieve this. The result was a set of architectural devices classified according to the kind of atmosphere created.